Heavy Metals Contamination in Rohu (Labeo rohita) from Fish Ponds of Mymensingh and Cumilla Regions in Bangladesh (Journal of the Bangladesh Agricultural University, 2025)
Water quality is a critical concern globally due to increasing threats from human activities. This study analyzed water, sediment, and fish (Labeo rohita) samples from the Cumilla and Mymensingh regions of Bangladesh. In this study, focusing on five trace elements (Cd, Cr, Cu, As, and Pb) to assess metal toxicity and identify potential sources. The average concentrations of As, Pb, Cd, Cr, and Cu in water were 4.43, 3.91, 201.00, 5.32, and 19.36 µg/L, respectively, while in sediments, the levels were 4.15, 16.8, 0.1, 17.19, and 23.86 mg/kg. In fish, the average concentrations were 0.97, 2.7, 1.31, 3.63, and 44.87 µg/g, respectively. The estimated daily intake of fish for males in Cumilla and Mymensingh was 0.34 mg/kg/d and 0.78 mg/kg/d, respectively, while for females, it was 0.36 mg/kg/d and 0.81 mg/kg/d, respectively. The hazard quotient assessment indicated that these levels did not exceed the recommended threshold, suggesting that consumers in these regions are unlikely to experience significant health risks from fish consumption. Studying heavy metals in water is crucial for informing policymakers because it provides the scientific foundation for setting safe water standards, protecting public health, and managing environmental impacts.J Bangladesh Agril Univ 23(2): 269-280, 2025